WorldFish: An Introduction - Rossignoli, Cristiano (WorldFish, 2022)
CGIAR is a global research partnership for a food secure future dedicated to reducing poverty, enhancing food and nutrition security, and improving natural resources. WorldFish's mission is to end hunger and advance sustainable development by 2030 through science and innovation to transform food, land and water systems with aquatic foods for healthier people and planet.